The History of the Decline and Fall of the Roman Empire : Table of Contents with links in the HTML file to the two Project Gutenberg editions (12 volumes) - Gibbon, Edward, 1737-1794; Milman, Henry Hart, 1791-1868; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2008)
"The History of the Decline and Fall of the Roman Empire" by Edward Gibbon is a six-volume historical work published between 1776 and 1788. This monumental chronicle spans from 98 to 1590, tracing the Roman Empire's peak through its collapse, early Christianity's rise as state religion, the fall of Byzantium, and the ascent of figures like Genghis Khan. Gibbon controversially argued that Christianity contributed to Rome's decline by weakening civic virtue, sparking debates that continue today about the true causes of empire's end. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_History_of_the_Decline_and_Fall_of_the_Roman_Empire
Release date is 2008-06-07
David Widger
Keywords: Rome -- History -- Empire, 30 B.C.-476 A.D.; Byzantine Empire -- History -- To 527; Indexes